Pharmacognostical and phytochemical analysis of Lepidium sativum L. seeds (International Current Pharmaceutical Journal, 2015)
Objective of the present study was to carry out the physicochemical and phytochemicals standardization of Lepidium sativum L seeds to establish the standard pharmacognostical parameters of this valuable medicinal plant. Many standardization parameters of Lepidium sativum were analyzed. Standard method was adopted for the preliminary phytochemicals screening. Analysis of pesticides residues, aflatoxin & heavy metals were also performed. The sections of seeds were prepared for quantitative microscopic parameters. The air dried powdered plant material was subjected for determination of physicochemical standardizations like ash value, Extractive value and fluorescence nature of the powder drug using light of short and long wavelength of 254nm and 366nm respectively. Phytochemical screening was performed for the identification of phytoconstituents in the plant which was helpful in the development of analytical profile. The morphological and microscopic examinations of drug were revealed the presence of endosperm cell which are polygonal in shape and contain alerone grains and oil droplet, cell of testa, yellow colouring matter and starch grains. Preliminary phytochemical screening showed the presence of carbohydrates, phenolic compounds, flavonoids, alkaloids, proteins, saponins and lipids in the drug extract and flourescence nature of drug was confirmed by fluorescence analysis in different solvent. Concentrations of heavy metals,ash value and extractive value were determined and found within acceptable Pharmacopoeial limits. Pesticides residues and aflatoxins were also determined but not detected in the tested samples. The physicochemical and phytochemical standards which are outcome of this research may be utilized as substantial data for identification and standardization of L. sativum seed.Ahmad et al., International Current Pharmaceutical Journal, September 2015, 4(10): 442-446